Implementation of the Mind Mapping Method to Enhance Explanation Skills in Basic Civic Education for Elementary Teacher Education Students at UIN Imam Bonjol Padang - Silvia Anggreni BP; Aulia Rahmi BP; Ekasyafutra (Global Action and Education for Society, 2025)
This study aims to examine the implementation of the mind mapping method to improve the ability to explain basic concepts of Civic Education (PKN) among students of the Primary School Teacher Education (PGMI) program at UIN Imam Bonjol Padang. The research employed a quantitative approach with a one-group pretest-posttest design. A total of 39 PGMI students participated as subjects. Data were collected through pretests and posttests measuring explanation skills, supplemented by observations during the learning process. The results indicated a significant improvement in students' explanation skills after the implementation of the mind mapping method. The average pretest score of 64.95 increased to 84.44 in the posttest, with a t-test analysis showing a statistically significant difference (p < 0.05). Observations also revealed that the mind mapping method enhanced student engagement, helped organize ideas more systematically, and boosted their confidence in delivering explanations. This study concludes that the mind mapping method effectively improves students' understanding and ability to explain basic PKN concepts. These findings support constructivist theory and are relevant for application in higher education learning contexts.